2021
DOI: 10.3389/fpsyg.2021.755490
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tempo on Temporal Expectation Driven by Rhythms in Dual-Task Performance

Abstract: Temporal expectation is the ability to focus attention at a particular moment in time to optimize performance, which has been shown to be driven by regular rhythms. However, whether the rhythm-based temporal expectations rely upon automatic processing or require the involvement of controlled processing has not been clearly established. Furthermore, whether the mechanism is affected by tempo remains unknown. To investigate this research question, the present study used a dual-task procedure. In a single task, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Conversely, a longer interval leads to predictions that are more variable and less precise, accompanied by increased uncertainty, which in turn results in a slower RT [ 48 ]. Additionally, these results align with the outcomes of our previous research, where younger adults exhibited faster RTs in response to fast-paced rhythm compared to slow-paced rhythm [ 27 , 28 , 43 ]. The possibility should also be considered that the mechanism of rhythm-based temporal expectations varies with tempo.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Conversely, a longer interval leads to predictions that are more variable and less precise, accompanied by increased uncertainty, which in turn results in a slower RT [ 48 ]. Additionally, these results align with the outcomes of our previous research, where younger adults exhibited faster RTs in response to fast-paced rhythm compared to slow-paced rhythm [ 27 , 28 , 43 ]. The possibility should also be considered that the mechanism of rhythm-based temporal expectations varies with tempo.…”
Section: Discussionsupporting
confidence: 90%
“…In our previous study (2021), we proposed that rhythm-based temporal expectation created by fast tempo relied on automatic processing. However, temporal expectations created by a slower tempo might engage more controlled processing, and memory-based strategies are employed to supplement the formation of temporal expectations [ 43 ]. Furthermore, recent studies have suggested that automatically processed rhythm-based temporal expectations are more effective in optimizing behavioural performance compared to memory-based temporal expectations that require more controlled attentional resources [ 27 , 28 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, concerning the cue sequence, it would be important to investigate how different inter-onset-intervals in beat sequences (here, IOI of 500 ms) might modulate the impact of beat cues on time estimation. Drake & Botte (1993) found that the highest sensitivity for tempo discrimination ranges between 300 ms to 800 ms and increased IOI worsens time performance, possibly reflecting a boundary between automatic (IOI of 300 ms) and more controlled processing (IOI of 3500 ms) proposed by Xu et al (2021). For instance, would accuracy in time estimation increase with a suboptimal (100 ms) or supraoptimal (1000 ms) beat cue?…”
Section: Discussionmentioning
confidence: 99%